2015
DOI: 10.1016/j.sbspro.2015.03.200
|View full text |Cite
|
Sign up to set email alerts
|

Enablers for Competitiveness of Indian Manufacturing Sector: An ISM-Fuzzy MICMAC Analysis

Abstract: Now a days global competitive scenario plays a critical role in success of Indian manufacturing sector. The present study argues that innovation can play a very important role in providing this competitiveness of Indian manufacturing sector. The study identifies 11 enablers for promotion of innovation in the Indian manufacturing sector. Based on the rigorous literature review 11 major innovation enablers (IEs) are obtained. The Delphi technique is applied as a potentially valuable tool for the grouping these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(51 citation statements)
references
References 66 publications
3
47
0
1
Order By: Relevance
“…It is evident from Table 3 that the technological factor is the most dominant factor responsible for nine drivers (D1, D2, D3, D4, D6.D9, D10, D11, and D12) of global manufacturing competitiveness. This is also in line with Dewangan et al (2015) who have identified" Technological Opportunities" as one of the enablers for achieving competitiveness of Indian manufacturing.…”
Section: Pest Analysissupporting
confidence: 85%
“…It is evident from Table 3 that the technological factor is the most dominant factor responsible for nine drivers (D1, D2, D3, D4, D6.D9, D10, D11, and D12) of global manufacturing competitiveness. This is also in line with Dewangan et al (2015) who have identified" Technological Opportunities" as one of the enablers for achieving competitiveness of Indian manufacturing.…”
Section: Pest Analysissupporting
confidence: 85%
“…ISM, as an appropriate analytical technique, is also helpful in identifying internal relationships between different variables. It can also be used in prioritising and analysing the effect of one factor on other factors (Attri et al., 2013; Dewangan et al., 2015). MICMAC analysis completes the interpretive-structural model by calculating the drive and dependent power of players (Dewangan et al., 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover this technique can also be implemented on multiple risk factors there by finding relationship among them. Also as an improvement to the current work we could even use ISM and fuzzy MICMAC technique [8]. Fuzzy logic deals with imprecision and the data available regarding floods and similar other natural disasters are imprecise in nature.…”
Section: Conclusion and Future Scopementioning
confidence: 99%